An element of work attribute that contributes to the employee satisfaction in Telekom Malaysia Berhad / Siti Saudah Ramlan - Ramlan, Siti Saudah (Faculty of Business and Management, 2006)
This research is about to explore an element of work attribute that contributes to the employee satisfaction in Telekom Malaysia Berhad. This is due to the commitment in performing the task has been decline lately. Thus the level of the absenteeism and come late into the office can be view as a problem arise that may affect the level of the satisfaction of the employee. Due to that, this research will explore to explore the element that most contributes to the employee satisfaction towards employees in TM Berhad, to explore the element that most contributes to the work attributes and to explore the elements that most contributes to the work attributes towards employee's satisfaction in TM Berhad. It consists of five elements that are efficiency, commitment, responsibility, nature of work and autonomy. At this research, probability and non-probability sampling techniques were been used to get the data that are require. Population of the research was employee at TM BHD and the sampling frame for this research is the employee at Menara TM, Kuala Lumpur. About 70 from 100 of respondents were getting from the research to help for accomplish this research. Then the finding indicates that productivity was most contribute to the employee satisfaction while efficiency was most contributes to the work attribute. Then there were two elements that most contributes to the work attribute towards employee satisfaction in TM BHD that are efficiency and commitment. Hopefully, the findings of this research can gives some benefits to the company so that they can make some improvement to increase their employee satisfaction.